A Behavior Sequence Analysis of Victims' Accounts of Stalking Behaviors. Issue 15 (August 2021) - Quinn-Evans, Leah; Keatley, David A.; Arntfield, Michael; Sheridan, Lorraine
Stalking is a complex issue involving multiple behaviors and interactions between the stalker and their target. Research has typically involved grouping risk behaviors related to stalking; however, the research question in the current research was to what extent a temporal method would allow investigators to map the dynamics of stalking. Behavior Sequence Analysis is a form of systems analysis that examines sequences of events over time, providing statistically significant results from complex real-world data. The Behavior Sequence Analysis method was applied to 39 participants' detailed accounts of stalking written in online forums. The study provides illustration of the antecedents of stalking and how it may initiate and develop through to end of contact. Both stalker behavior and decisions made by victim were included in the models. The results show multiple patterns of stalkers' behaviors; however, the results also clearly show that victims need not perform many behaviors for stalkers to continue with their actions. A main finding was how many behavior transitions occurred before victims felt a significant problem. A large number of participants indicated that they (repeatedly) reported their case of stalking to police and authorities; however, they were mostly dismissed or felt that police did not stop the stalker's actions. A major implication of the current research is providing a novel method to produce a framework that may be used to operationalize definitions of stalking based on coherent frameworks of stalkers' behaviors over time.